PET/CT: Current status in India - Rangarajan, Venkatesh (Medknow Publications, 2008)
PET/CT is a new modality with integration of PET and CT systems. In India, since December 2004 there has been a steady increase in the number of imaging systems. From stand-alone PET/CT systems with on-site cyclotrons, mostly in the government sector, the modality has matured to such an extent that, today, the majority of the PET/CT scanners and cyclotrons are in the private setup; also, scanners situated in different locations (and even different cities) share the isotope produced from one cyclotron. This shows how much this field has developed and reflects the confidence of the end users. The current status of PET/CT in India is indeed healthy and heartening and the future certainly looks promising.